1997
DOI: 10.2105/ajph.87.4.580
|View full text |Cite
|
Sign up to set email alerts
|

A community waterborne outbreak of salmonellosis and the effectiveness of a boil water order.

Abstract: OBJECTIVES: A 1993 large water-borne outbreak of Salmonella typhimurium infections in Gideon, Mo, a city of 1100 with an unchlorinated community water supply, was investigated to determine the source of contamination and the effectiveness of an order to boil water. METHODS: A survey of household members in Gideon and the surrounding township produced information on diarrheal illness, water consumption, and compliance with the boil water order. RESULTS: More than 650 persons were ill; 15 were hospitalized, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
2
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 14 publications
3
100
2
3
Order By: Relevance
“…Surprisingly, we found that nearly half our sample would drink tapwater, compared to 20 -31% in Angulo et al (1997) and O'Donnell et al (2000). In addition, the general noncompliance rate of 78% found here seems higher than the 64% reported for 'boil water' notices (O'Donnell et al…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Surprisingly, we found that nearly half our sample would drink tapwater, compared to 20 -31% in Angulo et al (1997) and O'Donnell et al (2000). In addition, the general noncompliance rate of 78% found here seems higher than the 64% reported for 'boil water' notices (O'Donnell et al…”
Section: Discussioncontrasting
confidence: 70%
“…We also found that men were more likely to display high risk behaviour and women were more likely to buy bottled water. The non-compliancy rates uncovered here are higher than those found by Winston et al (2003) and for 'boil water' notices (Angulo et al 1997;O'Donnell et al 2000) and it is essential that further studies are carried out.…”
Section: )contrasting
confidence: 47%
See 1 more Smart Citation
“…and Campylobacter spp. amongst others [40][41][42]. Studies carried out in different regions of Asia, Africa and South America have frequently pointed the unavailability of potable water for various activities at the vending site as a major concern.…”
Section: Watermentioning
confidence: 99%
“…Most infections result from the ingestion of foods of animal origin contaminated with Salmonella species such as beef, chicken, turkey, pork, eggs, and milk (D'Aoust 1997;D'Aoust 2000;Olsen et al 2000). Other vehicles, including non-animal foods such as fresh fruits and vegetables (Mahon et al 1997), reptiles (Friedman et al 1998), water (Angulo et al 1997), and direct person-to-person transmission (Lyons et al 1980), have also been implicated. However, certain serotypes of Salmonella such as S. Enteritidis, which can penetrate poultry reproductive organs resulting in the contamination of egg contents has been a prominent cause of human illness for several decades (Gantois et al 2009).…”
Section: Introductionmentioning
confidence: 99%